Distribution Characteristics of Long-Chain Branched Alkanes With Quaternary Carbon Atoms in the Carboniferous Shales of the Wuwei Basin, China - Xu, Li; Wang, Jiangong (Frontiers in Earth Science, 2022)
The branched alkanes with quaternary carbon atoms (BAQCs) and monomethylakanes (MMAs), cycloalkanes, monoethylalkanes (MEAs) have been detected by GC-MS in the saturated hydrocarbons fractions of Carboniferous black shale from the Wuwei Basin in northwest China. Nine series of BAQCs (series A-I) are present in Carboniferous black shale, which are concomitant with two series of long-chain cycloalkanes, two series of MMAs and one series of MEAs. All of these series are expressed as exclusively odd or exclusively even carbon numbers with consistent changes of abundance in the samples, meanwhile, based on the analysis of basic geochemical characteristics and other biomarkers of the samples, we presume that it possessed a similar parent materials or evolutionary process and weak oxidation-reduction sedimentation environments. In addition, the results show that the abundance of the long-chain branched alkanes is highly correlated with the odd-even predominances (OEP (15-19)) of the short-chain n-alkane. The lower the OEP (15-19) values of the short-chain n-alkane are (more significant the even-carbon dominance), the higher the abundance of the long-chain branched alkanes. The significant even-carbon dominance of the short-chain n-alkanes indicates the strong input of archaea or algal organic matter. The relatively wide occurrence and high abundance of these alkanes suggests a relationship with specific paleoenvironment and paleoclimate conditions.